Interleukin‐1β influences functional regeneration following nerve injury in mice through nuclear factor‐κB signaling pathway. Issue 3 (6th January 2019) - Wu, Ruoyu; Chen, Bi; Jia, Xiang; Qiu, Yu; Liu, Mengyu; Huang, Chengsheng; Feng, Jie; Wu, Qingkai
Summary: This study focuses on investigating the role of interleukin‐1 β (IL‐1 β ) in functional regeneration following nerve injury in mice. A microarray‐based mRNA profiling study was used to analyze the expression level of IL‐1 β in peripheral nerve regeneration. Quantitative real‐time polymerase chain reaction and Western blot were applied to assess the IL‐1 β expressions of C57BL/6J‐crush and C57BL/6J‐crush+IL‐1 β mice at different post‐injury time‐points after the standard sciatic nerve crush injury. The outcomes of nerve regeneration were evaluated by behavioral tests. IL‐1 β was found to be up‐regulated in peripheral nerve regeneration and significantly raised on the 3rd day and returned to normal levels on the 14th day after nerve injury. Compared with C57BL/6J‐crush+IL‐1 β mice, the nerve regeneration of C57BL/6J‐crush mice was worse after nerve crush injury. IL‐1 β increased mechanical sensitivity and stimulated amplitude. IL‐1 β could benefit the recovery of sciatic nerve crush injury by facilitating nerve regeneration. Abstract : We investigated the role of interleukin‐1 β (IL‐1 β ) in the process of neural functional regeneration. Our study revealed that IL‐1 β was likely to be significantly beneficial for both physical and functional recovery in injured periphery nerves through nuclear factor‐ κ B signaling pathway. This result extended our knowledge about the functions of IL‐1 β as well as the whole process of neural regeneration and provided new possibility for clinical treatments for nerve injury.